2022
DOI: 10.3389/fmed.2021.815870
|View full text |Cite
|
Sign up to set email alerts
|

Virological and Serological Characterisation of SARS-CoV-2 Infections Diagnosed After mRNA BNT162b2 Vaccination Between December 2020 and March 2021

Abstract: BackgroundVaccines for coronavirus disease 2019 (COVID-19) are proving to be very effective in preventing severe illness; however, although rare, post-vaccine infections have been reported. The present study focuses on virological and serological features of 94 infections that occurred in Lazio Region (Central Italy) between 27 December 2020, and 30 March 2021, after one or two doses of mRNA BNT162b2 vaccine.MethodsWe evaluated clinical features, virological (viral load; viral infectiousness; genomic character… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…In our opinion, this paves the way for an additional booster vaccine to restimulate waning immunity against SARS-CoV-2, especially in immunocompromised patients [84] or the frail elderly population. All 13 subjects reported mild symptoms at time of diagnosis, implying that vaccination protects against severe disease [85,86]. Notably, two subjects with reported BTI showed minimal SARS-CoV-2-specific vaccine-induced humoral and cellular responses at mid-term follow-up (Figure 7d,i) although these healthcare workers did not report compromised overall immunity.…”
Section: Discussionmentioning
confidence: 93%
“…In our opinion, this paves the way for an additional booster vaccine to restimulate waning immunity against SARS-CoV-2, especially in immunocompromised patients [84] or the frail elderly population. All 13 subjects reported mild symptoms at time of diagnosis, implying that vaccination protects against severe disease [85,86]. Notably, two subjects with reported BTI showed minimal SARS-CoV-2-specific vaccine-induced humoral and cellular responses at mid-term follow-up (Figure 7d,i) although these healthcare workers did not report compromised overall immunity.…”
Section: Discussionmentioning
confidence: 93%
“…Conversely, unvaccinated individuals were more likely to test positive for anti-N. Our low rate of positivity in vaccinated patients is similar to the report by Colavita et al, which demonstrated that only 6% of vaccinated patients were positive for anti-N at the time of diagnosis of a breakthrough infection. 17 Nucleocapsid protein is the first to undergo translation after infection and anti-N assays have been shown to be more sensitive in detecting infection compared to anti-Spike IgG. 18–20 Patients who tested positive for anti-N had a longer onset of symptoms prior to presentation compared to patients who tested negative (median of 10 vs 4 days) and could explain our observation.…”
Section: Discussionmentioning
confidence: 77%
“…However, as more variants emerge and replace prior ones, VOC and VOI classification periodically evolves and updates, with the aim of sharpening surveillance and research targets [ 4 ]. For example, in 2021, wild-type (WT) SARS-CoV-2 lineages and Gamma variant VOC co-circulated at a low prevalence simultaneously with the then predominant Alpha variant VOC, in Italy [ 10 , 11 ] as well as elsewhere [ 12 , 13 ]. As the new Delta variant VOC, emerged in India in 2020 [ 14 ], the superseded Gamma and Alpha VOCs [ 15 ] were downgraded to VOIs [ 9 ].Another variant, Omicron, first reported in South Africa and Botswana in early November 2021 [ 16 ], and all its subvariants are the main VOCs that are causing infections in Italy [ 15 ] as well as worldwide [ 13 ].…”
Section: Introductionmentioning
confidence: 99%